MEMBINCANG RELASI GENDER DALAM PERSPEKTIF KOMUNIKASI (Studi Kasus Terhadap Public Speaking Versus Private Speaking di Aceh Barat) - Muzakkir Muzakkir (SOURCE : Jurnal Ilmu Komunikasi, 2018)
The study and analysis in this paper based on addressing gender differences is common as long as it does not result in gender inequalities. In general, the notion of gender is a visible difference between men and women when viewed from values and behavior. In the Women Studies Encyclopedia it is explained that Gender is a cultural concept, seeking to make a distinction in terms of the roles, behaviors, mentality, and emotional characteristics of the growing male and female in society. However, reality in society indicates that gender differences give rise to various forms of inequality and injustice. Islam is a religion that strongly emphasizes the importance of respect for human beings and it seems his teaching is very accommodating to human values. One form of elaboration of human values is a sincere recognition of human equality and unity. The women of Rasulullah SAW era are described as active, polite, well-preserved women. In fact, in the Qur'an, the ideal figure of a Muslim is symbolized as a person who has independence in politics, like the figure of Queen Balqis who leads the superpower kingdom (`arsyun` azhim). Communication is the exchange of ideas, information, feelings or thoughts between people (individuals) face to face (face to face), verbal and non verbal. While counseling is a reciprocal relationship between two individuals, where a counselor is trying to help the other (the client) to try to solve the problems he is facing.Relation of gender is a social relationship between men and women who are socially formed and culture in doing everything. Based on the findings, it turns out that the meeting in West Aceh district, who want to appear in politics and to become ruler is still zero percent. Keywords: Gender Relations, Communications, Public Speaking, Private Speaking